Inputs of rare earth elements in Brazilian agricultural soils via P-containing fertilizers and soil correctives. (15th February 2019) - Silva, F.B.V.; Nascimento, C.W.A.; Alvarez, A.M.; Araújo, P.R.M.
Abstract: The mineral exploration of rare earth elements (REEs) and their entry into the soil via fertilizers has generated concern about environmental impacts and human health risks. We evaluated 60 samples of limestone, gypsum and phosphate fertilizers marketed in Brazil in order to characterize their contents, signature and solubility of REEs. The fertilizers from igneous origin presented the largest accumulation of REEs. Accumulation of the light REEs Ce, La, Nd, Pr, Sm and Eu were larger than the heavy REEs (Y, Dy, Gd, Er, Yb, Ho, Tb and Lu). The solubility of fertilizers produced from sedimentary sources was greater than that of igneous sources. The mean annual REEs contribution of SSP and organo-mineral + phosphate rock (both of igneous origin) to soils was > 4000 t year −1, with highest additions for Ce, La, Nd and Y. Thus, phosphate fertilization and liming were considered to be significant sources of REEs and soils receiving continuously high doses of these inputs are likely to be enriched in REEs. Risk assessment studies are necessary to evaluate the impact of these REEs additions to soils on human health. Highlights: Rare earth elements (REEs) in fertilizers and soil correctives were evaluated. Phosphate fertilizers were considered as significant sources of REEs for soils. Ce, La and Nd were more abundant in phosphate fertilizers of igneous origin. REEs in phosphate fertilizers of sedimentary origin showed high solubility. 13, 000 t year −1 REEs are incorporated annually to the agricultural soils.